Evaluation of the therapeutic effects of rehabilitation therapy on patients with amyotrophic lateral sclerosis—a meta-analysis - Cheng, Jianghua; Niu, Xiaomin; Li, Hui; Yang, Qiuwei; Du, Ketao (Frontiers in Neurology, 2024)
Objective To investigate the effect of rehabilitation therapy on the global function, respiratory function, and quality of life in patients with amyotrophic lateral sclerosis (ALS). Methods PubMed, Web of Science, and The National Library of Medicine (NLM) were systematically searched and the search period was between the date of database establishment and December 31, 2023. The outcome measures finally analyzed included the ALS functional rating scale/revised (ALSFRS/ALSFRS-R), forced vital capacity percentage predicted (FVC%), fatigue severity scale (FSS), and maximal expiratory pressure (MEP). Results A total of 13 randomized controlled trials (RCTs) were included, and 5 outcome measures were pooled and analyzed. A total of 657 patients with ALS were enrolled, with 299 in the experimental group (rehabilitation therapy, such as resistance training, endurance training, aerobic training, respiratory muscle training, and standard rehabilitation therapy) and 358 in the control group (conventional interventions, such as simple joint movements or daily stretching). The ALSFRS scores were better in the experimental group than in the control group at 0–4 months (MD = 3.36, 95% CI: 0.82, 5.91, Z = 2.59, p = 0.009) and at 5–8 months (MD = 5.00, 95% CI: −2.42, 7.58, Z = 3.80, p < 0.001). Moreover, the ALSFRS-R scores of the experimental group was better than that of the control group at 5–8 months (MD = 2.83, 95% CI: 1.21, 4.45, Z = 3.42, p < 0.001) and 9–12 months (MD = 1.87, 95% CI: −0.37, 4.11, Z = 1.63, p = 0.10). It was also found that the MEP value of the experimental group was significantly better than that of the control group after intervention (MD = 18.49, 95% CI: 1.47, 35.50, Z = 2.13, p = 0.03). However, there were no significant differences in FVC% value and FSS scores at 0–5 months and 6–12 months between the two groups. Conclusion Rehabilitation therapy is helpful in improving the short-, medium-, and long-term global function score of patients with ALS, with positive effects on respiratory function.